Behavioral Manifestations of Baby Blues Syndrome Among Postpartum Mothers in Muara District, North Tapanuli Regency - David Taufiq; Rianti Manda (PELNUS | Pen en Light for Natural Union of Science, 2024)
This research investigates the behavior of baby blues syndrome in postpartum mothers within Muara District, North Tapanuli Regency, Indonesia. Baby blues syndrome, characterized by transient emotional distress following childbirth, is a common yet often overlooked phenomenon impacting maternal mental health. Through a mixed-methods approach, incorporating quantitative surveys and qualitative interviews, this study explores the prevalence, risk factors, symptom profiles, coping mechanisms, and socio-cultural influences associated with baby blues syndrome in Muara District. Socio-economic disparities, lack of social support, marital discord, and cultural beliefs surrounding motherhood emerge as significant risk factors influencing the occurrence and severity of baby blues syndrome symptoms. Common symptoms include mood swings, irritability, tearfulness, anxiety, and feelings of sadness or emptiness, often exacerbated by fatigue and hormonal changes. Postpartum mothers employ various coping mechanisms, including seeking social support from family and community networks, engaging in traditional healing practices, and participating in religious or spiritual activities. Implications of the findings extend to clinical practice, public health policy, and future research endeavors. Healthcare providers are encouraged to adopt culturally sensitive approaches to screening, assessment, and intervention, ensuring the accessibility and acceptability of maternal mental health services.